Media Aplikasi Quizizz dalam Pembelajaran Ilmu Pengetahuan Sosial dan Pengaruhnya terhadap Hasil Belajar Peserta Didik - Medianto, Rizka; Arif, Muhamad; Nisa, Jakiatin (IJTIMAIYA: Journal of Social Science and Teaching, 2023)
This study aims to find out how the use of quizizz application media affects the learning outcomes of class VIII students at SMPN 189 Jakarta. The method in this research is quantitative experiment with the One Shot Case Study experimental design, in this study there is no control class and only one class sample will be given treatment. Data collection techniques in this study using test techniques, observation, questionnaire/ questionnaires and documentation. The results of the study are as follows: The results of the study show that the Quizizz Application variable and the Class VIII Student Learning Outcomes variable at SMPN 189 Jakarta have some of the results of the calculation analysis. The calculation of t count is reinforced by the results of the t count > t table or (9.506 > 1.697) and a significance value of 0.000 is less than 0.05, which means that Ha is accepted, and Ho is rejected with a significance value smaller than 0.05, namely (0.000 < 0, 05). So, it can be concluded that the Variable Use of the Quizizz Application partially has a significant influence on Learning Outcomes.